Answer:
Part A
[tex]Rate = -\frac{1}{2}\frac{\Delta A}{\Delta t} =-\frac{\Delta B}{\Delta t} = \frac{1}{3}\frac{\Delta C}{\Delta t}[/tex]
Part B
[tex]-\frac{\Delta B}{\Delta t}= 0.0500 M s^{-1} [/tex]
Part C
[tex]\frac{\Delta C}{\Delta t} = 0.15 M s^{-1}[/tex]
Explanation:
For a general reaction,
[tex]aA(g) + bB(g) \rightarrow cC(g)[/tex]
Rate is given by:
Rate: [tex]Rate = -\frac{1}{a}\frac{\Delta A}{\Delta t} =-\frac{1}{b}\frac{\Delta B}{\Delta t} = \frac{1}{c}\frac{\Delta C}{\Delta t}[/tex]
So, for the given reaction:
[tex]2A(g) + B(g) \rightarrow 2C(g)[/tex]
[tex]Rate = -\frac{1}{2}\frac{\Delta A}{\Delta t} =-\frac{\Delta B}{\Delta t} = \frac{1}{3}\frac{\Delta C}{\Delta t}[/tex]
Part B
[tex]-\frac{1}{2}\frac{\Delta A}{\Delta t} =-\frac{\Delta B}{\Delta t}[/tex]
Given: [tex]-\frac{\Delta A}{\Delta t} = 0.100\ Ms^{-1}[/tex]
[tex] \frac{1}{2}\frac{0.100}{\Delta t} =-\frac{\Delta B}{\Delta t}[/tex]
[tex]-\frac{\Delta B}{\Delta t}[/tex] = 0.0500 M s^-1
Part C
[tex]-\frac{\Delta B}{\Delta t} =\frac{1}{3}\frac{\Delta C}{\Delta t}[/tex]
[tex]-\frac{\Delta B}{\Delta t} =\frac{1}{3}\frac{\Delta C}{\Delta t}[/tex]
[tex]0.0500 = \frac{1}{3}\frac{\Delta C}{\Delta t}[/tex]
[tex]\frac{\Delta C}{\Delta t} = 3 \times 0.0500 = 0.15 M s^{-1}[/tex]